2005 IEEE International Workshop on Visual Surveillance and Performance Evaluation of Tracking and Surveillance
DOI: 10.1109/vspets.2005.1570929
|View full text |Cite
|
Sign up to set email alerts
|

Application and Evaluation of Colour Constancy in Visual Surveillance

Abstract: The problem of colour constancy in the context of visual surveillance applications is addressed in this paper. We seek to reduce the variability of the surface colours inherent in the video of most indoor and outdoor surveillance scenarios to improve the robustness and reliability of applications which depend on reliable colour descriptions e.g. content retrieval. Two well-known colour constancy algorithms -the Grey-World and Gamut-Mapping -are applied to frame sequences containing significant variations in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Obtaining color constancy is of importance for many computer vision applications, such as image retrieval, image classification, color object recognition and object tracking [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining color constancy is of importance for many computer vision applications, such as image retrieval, image classification, color object recognition and object tracking [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…Xiang and Gong have addressed the important issue of how to effectively recognise action in a surveillance context when there is a sparsity of example data [27] and what rรด le the high-level labelling of trajectories plays in this situation and in the general case [28]. Renno et al have expended considerable effort in creating solutions for a deployable, wide-area visual surveillance system and have addressed a variety of issues including themes such as colour constancy [19] and learning semantic models [17] in addition to the more common problems associated with surveillance, such as tracking. Notable work includes the investigation of how to track through blind regions, i.e., areas between camera views which cannot be seen in any view [2].…”
Section: Standard Methodsmentioning
confidence: 99%
“…Some of the most popular ones are the Grey-world assumption, which assumes that the spatial average of surface reflectances in a scene is achromatic and the Gamut-mapping, which recovers the transform that best projects the measured gamut into that of a canonical (see e.g., [10]). In [11] it is shown that both algorithms improve the color constancy for the visual surveillance scenario. The Grey-world method can be implemented in real time while the Gamut-mapping not.…”
Section: Human Recognitionmentioning
confidence: 99%